Pemberian Bantuan Hukum Terhadap Aparatur Sipil Negara di Kota Pekanbaru - Rezki Amellya; Sudi Fahmi; Ardiansah Ardiansah (Legalitas: Jurnal Hukum, 2021)
The purpose of the establishment of the government is to provide the best service in the context of meeting the needs of the community, to realize this a professional, responsible, honest and fair state civil apparatus is needed. In carrying out their duties and responsibilities, the state civil apparatus always deals with state administrative affairs, but not all state civil servants have the ability to understand the administrative competence and authority they have, so that it often leads to legal problems, when a state civil apparatus faces legal problems when carrying out its duties. In its duties, the state must be present to provide guarantees of legal protection by taking into account the presumption of innocence. The provision of legal assistance to state civil servants in Pekanbaru City who are involved in legal problems has not been implemented as stipulated in Law Number 5 of 2014 concerning State Civil Apparatus, this is because the Pekanbaru City Government does not have regulations and strategic plans in providing assistance law against the state civil apparatus so that it is necessary to accelerate and assist in accelerating the preparation and making of regulations in the context of providing legal assistance to the state civil apparatus in Pekanbaru City.